Automated Pressure-Controlled Discography in Patients Undergoing Anterior Lumbar Interbody Fusion for Discogenic Back Pain - Lee, Chang Kyu; Shin, Dong Ah; Kim, Hyoung Ihl; Yi, Seong; Ha, Yoon; Kim, Keung Nyun; Yoon, Do Heum (World neurosurgery, 2017)
Retrospective cohort study. To compare the clinical outcomes of patients undergoing anterior lumbar interbody fusion (ALIF) with or without automated pressure-controlled discography (APCD) before the procedure. Patients (n = 36) who underwent ALIF for lumbar discogenic back pain between 2008 and 2013 and were followed for more than 6 months were enrolled in this study. APCD was performed to identify discogenic back pain. Preoperative x-rays, computed tomography images, and magnetic resonance images were obtained. The intervertebral disc height, type of Modic change, grade of disc degeneration, and fusion rate were determined. Additionally, the presence or absence of high-intensity zone and vacuum disc were checked preoperatively. Clinical evaluation was performed by visual analog scale (0 = no pain, 10 = worst pain imaginable), Oswestry Disability Index (ODI), and 36-Item Short Form Health Survey before surgery and every 6 months postoperatively. The average patient age was 53.3 years (range, 31–73 years). The mean follow-up durations were 19.7 months. Seventeen patients (the APCD-ALIF group) underwent ALIF after APCD, and 19 patients underwent ALIF without APCD. The APCD-ALIF group had significantly improved clinical outcomes compared with the control group (visual analog scale score 1.8 ± 1.6 vs. 3.3 ± 2.4; P = 0.039: ODI score 6.7 ± 6.3 vs. 12.1 ± 6.8; P = 0.019). The surgical improvement rate was significantly associated with ODI score (P = 0.005). The results of this study confirm that APCD aids surgical outcomes of ALIF in patients with suspected lumbar discogenic pain. We recommend performing APCD before ALIF to confirm lumbar discogenic pain.